The Costs of Racism for Marriage: How Racial Discrimination Hurts, and Ethnic Identity Protects, Newlywed Marriages Among Latinos - Trail, Thomas E. (Pers Soc Psychol Bull, 2011)
The experience of racial or ethnic discrimination is a salient and severe stressor that has been linked to numerous disparities in important outcomes. Yet, the link between perceived discrimination and marital outcomes has been overlooked by research on relationship stressors. The current study examined this link and tested whether ethnic identity buffered the relationship between discrimination and ratings of marital quality and verbal aggression. A sample of 330 Latino newlyweds completed measures of perceived discrimination, ethnic identity, spouse’s verbal aggression, and marital quality. Each spouse’s interviewer also independently rated marital quality. Dyadic analyses revealed that husbands’ experience of discrimination negatively predicted wives’ marital quality, but only for husbands with weak ethnic identity. Wives whose husbands had strong ethnic identity were buffered from this effect. Identity also buffered the relationship between husband’s discrimination and verbal aggression toward their wives, and this effect mediated the relationship between discrimination, identity, and marital quality.